Prevalence and associated factors of infection in children with nephrotic syndrome aged 2-18 years in the northwest and east Amhara region, Ethiopia: a multi-center cross-sectional retrospective study - Birhanu Abie Mekonnen; Tilahun Dessie Alene; Yalemwork Anteneh Yimer; Ayenew Molla Lakew; Geta Bayu Genet (BMC Public Health, 2024)
Abstract Background Infection is the most common complication of pediatric patients with nephrotic syndrome. The factors associated with infection in nephrotic syndrome are lacking. The objective of the study was to identify the prevalence and associated factors among children with nephrotic syndrome aged 2 to 18 years. Methods We conducted a hospital-based retrospective cross-sectional study. The data collector installed an Epi5 collector electronic data-collecting tool from Google Play. Then, we exported the data to Stata version 15.1 for analysis. The mean, standard deviation, frequency, and percentage were used for descriptive statistics. The logistic regression model was used to identify the factors associated with infection. Results In this study, the prevalence of infection among nephrotic syndrome children is 39.8% (95%CI: 30.7, 49.7). The types of infection identified were pneumonia, urinary tract infection, diarrheal disease, cutaneous fungal infection, intestinal parasitic infection, and sepsis. The presence of hematuria increased the odds of infection by 5-times. On the other hand, low level of serum albumin increased the odds of infection by 7%. Being a rural resident increased the odds of infection by 3.3-times as compared to urban. Conclusions Serum albumin level, presence of hematuria, and rural residence were significantly associated with infection. We recommended a longitudinal incidence study on large sample size at multicenter to strengthen this finding.